WHERE EARTHLY-HEAVENLY LOVELIES: A STYLISTIC VIEW OF OSCAR WILDE'S THE SELFISH GIANT - Raed Fadhil (collage of education / university of Misan, 2022)
Albeit its deviant and dream-like nature, literature holds its humanitarian messages by and through its sign vehicle, i.e., language. This study purports to investigate the expressive and impressive powers that represent the purposive image of reality, more specifically the clause processes that are dominant in Oscar Wild's The Selfish Giant. Special attention is paid to the figures of style which portray the landscape of the fairy tale. The narrative text is described, analyzed, and interpreted in terms of Halliday's Systemic Functional Linguistics (SFL) as a theoretical framework to detect the predominant clause processes in the body of the narrative structure. The study proceeds with the hypothesis that a fairy tale is not merely a sequence of interrelated linguistic options; it is humanity pained and encoded into a creatively imaginative piece of art. The paper concludes that the stylistic analysis has shown the frequent co-occurrences of the Material and Mental clause processes, whereas bodily actions are not without the patterns of cognition and perception. Then, Relational clause processes are less used in The Selfish Giant. Still, the clause processes are not the only stylistic aspects of The Selfish Giant. All the reciprocal interactions in the linguistic structures lead to the production of meaning proper, the ultimate aim of the stylistic exploration.